The institutional work of Own the Podium in developing high performance sport in Canada - Dowling, M.; Smith, J. (Journal of Sport Management, 2016)
This investigation examined how Own the Podium (OTP) has contributed towards the ongoing development of high performance sport in Canada. In adopting an institutional work perspective, we contend that OTP's continuance has not been the sole product of Canada's success at the Olympic and Paralympic Games or lobbying efforts to secure additional funding. Rather, OTP's permanence can also be explained as the by-product of the activities and actions of OTP itself and its supporting stakeholders to embed and institutionalize both the organization specifically and high performance sport more generally into the Canadian sport landscape. In short, OTP's continued existence can, in part, be explained by ongoing institutional work. To support our contentions, we draw upon and analyze documentation that was either produced by, or significant to the development of, OTP. Our analysis identifies a number of OTP-related practices (e.g., tiering, hiring of high performance advisors, and the creation and support of new high performance sport programs) that have further institutionalized OTP and the norms, routines and practices associated with high performance sport. More broadly, our investigation draws attention to the importance of individual and collective actors in shaping institutional settings within sport.